The Aesthetics of Narrative Immersion. Marie-Laure Ryan’s New Anatomy of Storyworlds - Jon Hegglund (Diegesis: Interdisziplinäres E-Journal für Erzählforschung, 2023)
Review of: Marie-Laure Ryan. A New Anatomy of Storyworlds: What Is, What If, As If. Columbus: Ohio State University Press, 2022. 248 pp. USD 89.95. ISBN 978-0-8142-1508-1